The Effect of Product Quality, Price, Sales Promotion, and Trust Towards Consumers' Purchase Decision in Dey's Recipe - Adelia Puspa Kirana (Universitas Ciputra Surabaya, 2022)
The purpose of this study was to determine, test, and analyze the effect of product quality, price, sales promotion, and customer trust on purchasing decisions at Dey's Recipe. The population in this study are all Dey's Recipe customers who have made purchases from June 2020 to March 2021 as many as 73 respondents. The sampling technique that will be used in this research is the Saturated Sampling Method. Data collection techniques using a questionnaire and measured using a Likert scale. The number of samples in this study was 73. The data analysis method used was quantitative with multiple linear regression models and processed using SPSS. The results of the study show that product quality has a positive but not significant effect on purchasing decisions on Dey's Recipe. Meanwhile, price, sales promotion, and customer trust have a positive and significant influence on purchasing decisions in the Dey's Recipe business.